Country-level business performance and policy asymmetries in the UK. (21st August 2008) - Plumridge, Anthony; Webber, Don J.; Boddy, Martin; Hudson, John
The HM Treasury identifies the key 'drivers' of business performance and productivity differentials, which include skills, investment and competition. This paper presents an empirical investigation into the effects of these drivers on business-level productivity per employee across England, Scotland and Wales in order to identify whether spatial differences in the influence of these drivers exist. We adopt the Cobb-Douglas production function approach and our results suggest that, after taking account of sector-specific effects, productivity differentials do exist between businesses across the UK and that policy instruments do potentially enhance productivity. The results indicate that these key drivers are equally applicable across the countries of the UK. However, there is evidence to suggest that the scale effects for labour and capital do differ across England, Wales and Scotland and that policy-makers should be aware of these asymmetries.